Pemahaman Siswa Kelas V SD Negeri Malangan terhadap Konsep Sumber Daya Alam Dapat Diperbarui dan Tidak Dapat Diperbarui - Theresia Indah Septalia; Azamul Fadhly Noor Muhammad (STKIP Subang, 2026)
This study aimed to describe the level of understanding of fifth-grade students at SD Negeri Malangan regarding renewable and non-renewable natural resources. A qualitative descriptive approach was employed to obtain a comprehensive picture of students’ conceptual understanding. The participants consisted of 17 fifth-grade students. Data were collected through concept comprehension tests, semi-structured interviews, and learning documentation. The collected data were analyzed through data reduction, data display, and conclusion drawing. The findings revealed that students’ understanding varied across categories. Five students (29.41%) demonstrated a high level of understanding, eight students (47.06%) were categorized as moderate, and four students (23.53%) showed a low level of understanding. Most students were able to identify examples of natural resources; however, many experienced difficulties explaining the scientific basis used to classify natural resources as renewable or non-renewable. Interview results also indicated the presence of misconceptions, particularly regarding the formation processes and availability of certain natural resources. Furthermore, learning activities that incorporated environmental contexts and students’ daily experiences were found to support better conceptual understanding. These findings suggest the importance of contextual learning strategies to strengthen students’ understanding of natural resource concepts and minimize misconceptions in science education at the elementary school level.